Design Recommendation Information Architecture of Hospital Website Using Bottom-Up Approach on Card Sorting Method - Risqi Puspa Dewi; Mira Kania Sabariah; Veronikha Effendy (International Journal on Information and Communication Technology (IJoICT), 2019)
One of the public facilities that use websites is the hospital. However, there are some shortcomings complained by users related to the hospital website, which is the lack of information, confusing view of the menu, etc. Therefore, we need the information architecture to manage related content and website structure. The build of information architecture is done by using a bottom-up approach in card sorting. There are five stages in the research, which the first stage is a strategy to equalize the goal in the development of the hospital website either from the point of view of the organization or company and the user's point of view of the hospital website. The second stage is a scope to find out what are the needs of the user in order to build the hospital website. The third stage is structure, which is the formation of the initial structure of information architecture by using a bottom-up approach to the card sorting method. The type of card sorting that is commonly used is the open card sorting. The fourth stage is the skeleton stage, which is used to make information architecture model design using wireframe and prototype. The fifth stage is the test using findability testing and usability testing. From the test, the design of information architecture is made to fulfill the desires and needs of users, as proven by the results of findability testing achieved 15.9 seconds, and the results of usability testing achieved 80.33. Hence, by the results of these tests, it can be concluded that the design of information architecture at the hospital website has a good value from findability testing and usability testing.